Ciri Kejuruteraan Asfalt Berliang Akibat Tindakan Pengusiaan Jangka Pendek Dan Jangka Panjang - Wan, Che Norazman Che (2010)
Porous asphalt is widely applied to improve road safety and reduce traffic noise. A number of studies have been carried out to improve the performance of porous asphalt, including its properties when exposed to ageing. The objective of this study is to evaluate the engineering properties of porous asphalt when subjected to short term and long term ageing. A proposed gradation was developed based on the porous gradation analysis that has been successfully applied in other countries. The JKR gradation was included in this study as a control.